PENGARUH PEMBERIAN REWARD TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA SDN JATIMULYA 06 - Caroline Anasthasia Situmorang, Cyntia; Rosyid, Ainur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Rewarding is a learning strategy aimed at motivating students to be more active, disciplined, and achieve through praise, grades, or awards for certain achievements. Although many studies focus on rewards in exact subjects, a different phenomenon was found at SDN Jatimulya 06, especially in classes VA and VB which implemented different reward variations. The VA class teacher used various types of rewards such as points, small gifts, and routine reflections, while the VB class teacher only gave verbal praise and star cards. This quantitative research using a survey method aimed to determine the effect of rewarding on the learning outcomes of fifth-grade students in the Pancasila Education subject. The instruments used included a questionnaire to measure reward acceptance and documentation of test scores as an indicator of learning outcomes. The sample consisted of 35 fifth-grade students at SDN Jatimulya 06. The results of the partial test (t-test) showed a t-count of 2.283, greater than the t-table of 2.034 with a significance of 0.029 <0.05. This means that H0 is rejected and H1 is accepted, so it can be concluded that giving rewards has a significant effect on the learning outcomes of fifth grade students in the Pancasila Education subject at SDN Jatimulya 06.